Penafsiran Sayyid Qutb terhadap Amthâl al-Qur’ân dalam Tafsîr Fî Zilâl al-Qur’ân Putri Alfiah Halida - Alfiah Halida, Putri (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2013)
In conveying messages of teachings, the Koran uses a variety of ways. One of the ways in which the Koran is using amthâl. Amthâl al-Qur’ân is the message of the Koran are delivered with parables, which likens abstract things with concrete, with the aim that the messages easier to understand. This article will specifically dissect the interpretation of Sayyid Qutb against amthâl al-musarrahah in Fî Zilâl al-Qur’ân using thematically, as judged able to know fully and comprehensively the purpose of a theme discussed. The purpose of the amthâl al-musarrahah is a parable in which is described by the word mithâl or something that shows tashbîh. In the Koran, the verses relating to amthâl al-musarrahah found 22 verses are included in the classification amthâl al-makkîyah and 20 verses amthâl musarrahah included in the classification amthâl al-madanîyah. However, this article will only discuss the interpretation of Sayyid Qutb in QS. al-Rûm [30]: 27, QS. al-Ra‘d [13]: 17 and 35, QS. al-Nûr [24]: 35, and QS. Muhammad [47]: 1-3 and 15